Efficient anaerobic digestion of a mild wet air pretreated molasses ethanol distillery stillage: A comparative approach. Issue 11 (November 2020) - Gebreeyessus, Getachew Dagnew; Sreekrishnan, Trichur Ramaswamy; Mekonnen, Andualem; Chebude, Yonas; Alemayehu, Esayas
Abstract: The effect of a mild, wet air pretreatment and the subsequent anaerobic digestion (AD) was examined on the recovery of a complex and toxic molasses ethanol distillery stillage. The biogas yield and organics removal due to pretreatment were compared with the raw stillage AD. The application of a scoria support in this industrial residue AD process stability was also assessed. Consequently, a statistically significant cumulative specific methane recovery difference (p-value = 0.000) with an almost complete biological oxygen demand (BOD) removal and a significant chemical oxygen demand (COD) reduction, which were 100% and 92% respectively were achieved. Additionally, the biogas recovery rate was hastened due to pretreatment. The application of scoria, whose property has been instrumentally inspected, has helped stabilize the pH in the AD systems. In a comparative approach, this study suggests the energy benefit and an ecofriendly discharge of stillage by the ethanol industry towards sustainability. Abstract : Chemical engineering; Bioengineering; Environmental science; Environmental engineering; Environmental hazard; Environmental health; Environmental management; Environmental pollution; Environmental risk assessment; Environmental toxicology; Biogas; Chemical oxygen demand; Scoria; Stillage; Wet air pretreatment.